Teachers and students' views prior to introducing inquiry-based learning in Qatari science and mathematics classrooms. (August 2021) - Murphy, Carol; Abu-Tineh, Abdullah; Calder, Nigel; Mansour, Nasser
Abstract: Teachers and students' dispositions have a major influence towards the introduction of inquiry-based learning (IBL). In this study we present analysis of pre professional development interview data from teachers (n = 16) and student focus groups (n = 96) as part of a larger project to promote IBL in Qatari middle school mathematics and science classrooms. Teacher and student responses suggested contrasting perspectives related to stress factors and goal orientations. Implications of the findings suggest the need to consider teacher and student subjectivities in transforming teaching practice. Highlights: The role of teacher development in inquiry-based learning is not straightforward. Teachers and students may experience stress factors in implementing inquiry. Stress factors relate to teacher and student short or long-term learning goals. Teacher and student subjectivities are considered in addressing stress factors.